Sambang Bayi Behavior among the Osing Tribe in Banyuwangi Regency and Its Impact on Maternal and Infant Health - Nur, Zilvi Fuadiyah; Widati, Sri; Nurmala, Ira; Iken Nafikadini, Iken; Rokhmah, Dewi (Journal of Maternal and Child Health, 2023)
Background: Banyuwangi Regency is home to several cultures, and when babies are born, their families quickly prepare all the necessary equipment, showing their joy by rushing to complete the task. This creates a dense sambang bayi behavior in the area, however such activities may pose risks to the health of both the mother and the baby. This study aimed to analyze the sambang bayi behavior among the Osing tribe in Banyuwangi Regency and its impact on the health of both the mother and the baby.Subjects and Method: To investigate this phenomenon, a qualitative method using an ethno-graphic research approach was employed. Postpartum were researched at the Singojuruh and Gladag Health Centers. 12 main informants and 6 additional informants were selected using purposive sampling. Data was collected through in-depth interviews, participatory observation, and documentation, and analyzed thematically using content analysis.Results: The research revealed that postpartum perceived vulnerability, seriousness, advantages, and obstacles related to cultural activities. Additionally, they made efforts to reduce health risks to their infants (cues to action).Conclusion: Several health risks were identified for mothers and babies, including allergies, irritation, respiratory problems, infectious diseases such as coughs and colds, and diseases caused by a lack of rest. To mitigate these risks, the community can implement promotive and preventive efforts. Keywords: postpartum, culture, perception. Correspondence: Zilvi Fuadiyah Nur. Masters Program in Public Health, Airlangga University. Jl. Dr. Ir. H. Soekarno, Mulyorejo, Kec. Mulyorejo, Kota SBY, Jawa Timur 60115. Email: zilvi.fuadiyah.nur-2022@fkm.unair.ac.id. Mobile: 082330870755.